Important Factors of Automated Monitoring of Quality and Quantity in Construction Projects - Wong, Kai Wing (Universiti Teknologi PETRONAS, 2020)
Progress monitoring is one of the critical tasks in the construction project. It is crucial to monitor the work of the construction project and identify any discrepancies which may lead to time and cost overrun. The current practice of progress monitoring is mainly based on daily manual site inspection and collection of site progress photos and site videos. Several limitations are found in this practice such as tedious and error during the inspection. Comparatively, progress monitoring using automation tools is fast and accurate. Undoubtedly, automated progress monitoring is not well-matured, and several factors are found which limits the effectiveness and efficiency of progress monitoring in a construction project. Thus, this study aims to investigate the important factors for automated monitoring of quality and quantity in construction projects. This study will only focus on building structures and cover different types of automation tools in progress monitoring such as photogrammetry, videogrammetry, RFID and laser scanning.